Empowering the Future Workforce: How Self-Concept and Career Attitudes Shape Readiness Among Undergraduate Interns - Alifiana, Mia Ajeng; Nastiti, Tur; Wibowo, Nadia Utami; Sokhibi, Akh.; Lusianti, Dina; Prihandono, Agung (Jurnal Pendidikan Progresif, 2026)
This study examines the relationship between self-concept (self-management and self-esteem) and career readiness among students participating. It examines the mediating role of career attitudes in this relationship by testing five hypothesized pathways. The internship experience is positioned as a structured learning context that supports the development of self-regulation and positive self-evaluation. A quantitative, cross-sectional survey design was used to examine the role of self-concept in career readiness. Data were collected by online questionnaire from 8,877 undergraduate students who participated in the now-concluded national internship program “Certified Internship and Independent Study (MSIB) in its fifth cohort (2023). Data analysis was conducted using multiple regression and path analysis in SmartPLS 4.0 to test relationships and mediation effects. The results showed that both components of self-concept, self-management (β = 0.427, p < 0.001) and self-esteem (β = 0.265, p < 0.001) had significant, positive effects on career readiness. In addition, self-management (β = 0.536, p < 0.001) and self-esteem (β = 0.333, p < 0.001) were positively associated with career attitudes, which, in turn, were significantly associated with career readiness (β = 0.380, p < 0.001). Mediation analysis confirmed that career attitudes partially mediate the relationship between self-management, self-esteem, and career readiness. The research model explained 74.0% of the variance in career readiness (R2 = 0.740), indicating that the constructs studied are substantial predictors of students' work readiness. According to the study’s findings, to make students career-ready, it is necessary to adopt a two-fold approach. First, enhancing self-esteem through positive internship experiences and constructive criticism. Second, providing students with structured internship programs to help them develop self-regulatory skills. To maximize graduates' readiness to enter the workforce, higher education institutions are advised to design career development programs that simultaneously enhance self-management skills, foster adaptive professional attitudes, and promote healthy self-esteem by integrating these programs into the core curriculum, permanent career services, and a standardized internship reflection system. Keywords: career readiness; internship; self-concept; career attitudes; undergraduate students.